2017
DOI: 10.3389/fnmol.2017.00086
|View full text |Cite
|
Sign up to set email alerts
|

Efr3a Insufficiency Attenuates the Degeneration of Spiral Ganglion Neurons after Hair Cell Loss

Abstract: Sensorineural hearing loss (SNHL) is caused by an irreversible impairment of cochlear hair cells and subsequent progressive degeneration of spiral ganglion neurons (SGNs). Eighty-five requiring 3 (Efr3) is a plasma membrane protein conserved from yeast to human, and knockout of Efr3a was reported to facilitate the survival of hippocampal newborn neurons in adult mice. Previously, we found Efr3a expression in the auditory neural pathway is upregulated soon after the destruction of hair cells. Here we conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Morphological observations (Figures 1 and 2) showed that a single injection of kanamycin sulfate (1 g/kg) and an intraperitoneal injection of furosemide (0.4 g/kg), which was injected 30~45 min after the kanamycin injection, successfully induced SGN degeneration in the cochlea of mice via the destruction of cochlear sensory epithelial cells, which was consistent with the results of our previous studies [19,20]. The structure of the organ of Corti was completely collapsed and disintegrated, nearly no sensory epithelial cells remained on the 30th day after kanamycin and furosemide administration, and the basilar membrane was covered by a continuous layer of flattened cubic epithelial cells.…”
Section: A Mouse Model Of Sgn Degeneration Was Successfully Establishsupporting
confidence: 89%
See 4 more Smart Citations
“…Morphological observations (Figures 1 and 2) showed that a single injection of kanamycin sulfate (1 g/kg) and an intraperitoneal injection of furosemide (0.4 g/kg), which was injected 30~45 min after the kanamycin injection, successfully induced SGN degeneration in the cochlea of mice via the destruction of cochlear sensory epithelial cells, which was consistent with the results of our previous studies [19,20]. The structure of the organ of Corti was completely collapsed and disintegrated, nearly no sensory epithelial cells remained on the 30th day after kanamycin and furosemide administration, and the basilar membrane was covered by a continuous layer of flattened cubic epithelial cells.…”
Section: A Mouse Model Of Sgn Degeneration Was Successfully Establishsupporting
confidence: 89%
“…Unlike gentamicin (another aminoglycoside drug), which damages hair cells and nerve fibers simultaneously [48], kanamycin does not directly damage mature SGN. With electron and light microscopy, in our previous studies, we found that kanamycin and furosemide destroyed the cochlear sensory epithelial cells of adult mice in a very short period and did not directly injure the soma of SGNs [19,20]. In our previous study about the reinnervation of the regenerated hair cells in the cochleae of chickens, the TEM results showed that the morphological structures of synapses beneath the injured hair cells were normal [44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations